1999
DOI: 10.1023/a:1006131506193
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Up to 80% of Zea mays L. grain phosphorus is stored in the form of phytin in the embryo. Our objective is to determine the control of phytin mobilization during germination and seedling growth. A maize phytase cDNA, phy S11, has been previously characterized (Maugenest et al., Biochem J 322: 511-517, 1997). In the present work, phy S11 was used to screen a maize genomic library and two distinct genes, PHYT I and PHYT II, were isolated and sequenced. The transcribed sequences of these two genes presented a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It was shown that phytases exist in multiple chromatographic forms in germinated lupine seeds. Multiple forms of phytases have already been identified in other plant species, such as barley (), wheat ( 23 , 36 , 37 ), spelt (), maize ( , ), rice (), soybean (), rapeseed (), pumpkin (), and lily ().…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that phytases exist in multiple chromatographic forms in germinated lupine seeds. Multiple forms of phytases have already been identified in other plant species, such as barley (), wheat ( 23 , 36 , 37 ), spelt (), maize ( , ), rice (), soybean (), rapeseed (), pumpkin (), and lily ().…”
Section: Discussionmentioning
confidence: 99%
“…Screening a maize phage display library with this antibody yielded the first plant phytase nucleotide sequence ( PHYT I ): a HAP [ 68 ]. The subsequent screening of a maize genomic library using the cDNA clone as a probe provided two highly homologous genes ( PHYT I and PHYT II ) [ 69 ]. The two genes were shown to have an overlapping expression pattern, with PHYT I having the highest expression level.…”
Section: Phytasesmentioning
confidence: 99%
“…A lower, but consistent, signal remained detectable in the roots after one month. The immunolocalization of the proteins revealed a similar pattern [ 69 ]. PHYT-I was expressed in E. coli .…”
Section: Phytasesmentioning
confidence: 99%